SYNTHESIS AND CHARACERISATION OF NOVEL PENTADENTATE LIGAND TYPE N2S2O 4-METHYL-2,6- BIS[4-METHYL THIOSEMICARBAZONYLIDEN]- PHENOL AND THEIR COMPLEXES WITH Ni+2 , Pd+2 , Cu+2 , Zn+2 , Cd+2 and Hg+2 - Mohy, Taghreed; Musa, Aldin (Al-Nahrain Journal of Science, 2018)
Two equivalent of 4-methyl thiosemicarbazide was reacted with 2,6-diformyl-4-methyl phenol to give the new pentadentate ligand H3L type N2S2O {where H3L= 4-methyl-2,6- Bis[4-methyl thiosemicarbazonyliden]-phenol. Also complexes of the ligand of H3L in general formula [M HnLX]y where M=Ni+2 , Cu+2 , n=2, X=Cl, y=0; M=, pd+2 , Zn+2, Cd+2 and Hg+2 ions , n=3, X=0, y=+2 were prepared. All complexes and ligand have been characterised by spectroscopy methods {IR, UV-Vis, 1H, 13C, 1H13C NMR spectroscopy}, atomic absorption, microanalysis of elements (C.H.N), along with conductivity measurement. From the above data, the proposed molecular structure for Ni+2 and Cu2 ions are octahedral, pd +2 complexes is square planner, while Zn+2 ,Cd+2 , Hg+2 complexes are forming distorted tetrahedral.